Proceedings of the International Scientific Conference - Sinteza 2016 2016
DOI: 10.15308/sinteza-2016-1-9
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Development of Informatics Curricula Based on Semantic Technologies

Abstract: Abstract:In order to keep pace with the ongoing changes in ICT and increasing common IT competencies requirements, informatics curricula at secondary school level and, consequently, curricula educating informatics teachers must be frequently changed to ensure necessary competencies. This paper proposes collaborative development of informatics curricula assisted by a software tool for compatibility analysis of secondary school informatics curricula and curricula by which teachers of informatics are educated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In this section the results obtained by comparing teacher education curricula are analyzed regarding the results obtained by comparing the secondary ACM K12 curriculum model and the teacher education reference curriculum model [16], and regarding the results obtained by comparing secondary ACM K12 curriculum model and the chosen teacher education curriculum model [24] in the manner described in [17]. The values of precision, recall and F-measure for all three combinations of input ontological models are shown in Figure 8.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this section the results obtained by comparing teacher education curricula are analyzed regarding the results obtained by comparing the secondary ACM K12 curriculum model and the teacher education reference curriculum model [16], and regarding the results obtained by comparing secondary ACM K12 curriculum model and the chosen teacher education curriculum model [24] in the manner described in [17]. The values of precision, recall and F-measure for all three combinations of input ontological models are shown in Figure 8.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…From the literature review, it can be concluded that there are a number of papers dealing with curriculum alignment, curriculum ontological representation and ontology alignment. However, to our knowledge, only curricula synchronization platform, presented in [16] [17], is made on the basis of ontology alignment methods. The platform for the harmonization of teacher education curriculum software, presented in this paper, uses a different input ontological model compared to those presented in [16] [17].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations